Leonore A. Grenoble y Lindsay J. Whaley. Saving Language. An introduction to language revitalization - Becerra, Rukmini; Hasler, Felipe (Lenguas Modernas, 2011)
New York: Cambridge University Press 2006, 245 páginas. ISBN 978-0-511-12936-0